2011
DOI: 10.1039/c1jm10312a
|View full text |Cite
|
Sign up to set email alerts
|

Silicate cathodes for lithium batteries: alternatives to phosphates?

Abstract: Polyoxyanion compounds, particularly the olivine-phosphate LiFePO 4 , are receiving considerable attention as alternative cathodes for rechargeable lithium batteries. More recently, an entirely new class of polyoxyanion cathodes based on the orthosilicates, Li 2 MSiO 4 (where M ¼ Mn, Fe, and Co), has been attracting growing interest. In the case of Li 2 FeSiO 4 , iron and silicon are among the most abundant and lowest cost elements, and hence offer the tantalising prospect of preparing cheap and safe cathodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
303
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(314 citation statements)
references
References 48 publications
8
303
0
3
Order By: Relevance
“…A new family of cathode materials have been presented recently based on the tetrahedral orthosilicates which, theoretically, are capable of a two electron intercalation process involving the M 4+/3+ and M 3+/2+ redox couples [492,493]. The dual-electron process may therefore yield cathodes with capacities exceeding 300 mA h g -1 , while the relative strength of the Si-O bond may impart a necessary structural stability.…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 99%
“…A new family of cathode materials have been presented recently based on the tetrahedral orthosilicates which, theoretically, are capable of a two electron intercalation process involving the M 4+/3+ and M 3+/2+ redox couples [492,493]. The dual-electron process may therefore yield cathodes with capacities exceeding 300 mA h g -1 , while the relative strength of the Si-O bond may impart a necessary structural stability.…”
Section: Transition Metal Silicates (Li2msio4)mentioning
confidence: 99%
“…29 They also found the tetrahedral structure to stabilize VO 4 4-. Up to date, experimental studies of V doping in shows phase separation into V and Fe containing spinel phases at higher doping levels of V in Li 2 FeSiO 4 , and a general decay of the electrochemical properties. 30 Zhang et al substituted up to 7 mol % V on the Fe-site of Li 2 FeSiO 4 and found a strong increase of electrochemical properties for 5 mol % V substitution.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, experimental studies of V doping in shows phase separation into V and Fe containing spinel phases at higher doping levels of V in Li 2 FeSiO 4 , and a general decay of the electrochemical properties. 30 Zhang et al substituted up to 7 mol % V on the Fe-site of Li 2 FeSiO 4 and found a strong increase of electrochemical properties for 5 mol % V substitution. 31 At the same time their XRD data shows that almost all major Li 2 FeSiO 4 diffraction peaks diminish at increased V concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In these silicates, oxide ions form a pseudo-hexagonal closed packed (hcp) structure. The cations occupy a half of its tetrahedral sites and show several kinds of ordered arrangements depending on the transition metals species and the heat treatments during the sample preparation.…”
Section: Introductionmentioning
confidence: 99%